2014
DOI: 10.1037/a0037231
|View full text |Cite
|
Sign up to set email alerts
|

Back to basics: A naturalistic assessment of the experience and regulation of emotion.

Abstract: Emotion regulation research links regulatory responding to important outcomes in psychological well-being, physical health, and interpersonal relations, but several fundamental questions remain. As much of the previous research has addressed generalized regulatory habits, far less is known about the ways in which individuals respond to emotions in daily life. The literature is particularly sparse in explorations of positive emotion regulation. In the current study, we provide an assessment of naturalistic expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
291
5
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(348 citation statements)
references
References 64 publications
24
291
5
3
Order By: Relevance
“…Another possible reason for the discrepancy between past research and current findings was the absence of a forced choice in the present study. Recent work finds that, when possible, participants report using multiple ER strategies in response to brief stressors (e.g., Aldao & Nolen-Hoeksema, 2013;Heiy & Cheavens, 2014). Our findings mirror recent research indicating low endorsement of reappraisal even at low emotional intensities (Suri, Whittaker, & Gross, 2014), presumably due to hidden costs (such as the high level of required effort) associated with this strategy.…”
Section: Discussionsupporting
confidence: 89%
“…Another possible reason for the discrepancy between past research and current findings was the absence of a forced choice in the present study. Recent work finds that, when possible, participants report using multiple ER strategies in response to brief stressors (e.g., Aldao & Nolen-Hoeksema, 2013;Heiy & Cheavens, 2014). Our findings mirror recent research indicating low endorsement of reappraisal even at low emotional intensities (Suri, Whittaker, & Gross, 2014), presumably due to hidden costs (such as the high level of required effort) associated with this strategy.…”
Section: Discussionsupporting
confidence: 89%
“…coded each response as one of 30 categories, based primarily on a previous study of a wide range of emotion regulation strategies (i.e., Heiy & Cheavens, 2014; Table 2). Ten categories not assessed by Heiy and Cheavens (2014) were generated by the study authors before coding but after reviewing a subset of participant responses to ensure adequate conceptual coverage (i.e., express emotions, information gathering, isolation, leave the situation, nothing - wait to feel better, prayer, reflection, relationship antagonism, relationship maintenance/repair, and therapy/counseling). Raters coded each participant’s set of five responses in order, but sets were randomized by participant and vignette.…”
Section: Methodsmentioning
confidence: 99%
“…Larger emotion regulation repertoires have been associated with fewer symptoms of depression (Herman-Stahl, Stemmler, & Petersen, 1995), as well as lower momentary negative affect and greater momentary positive affect (Heiy & Cheavens, 2014). …”
Section: Emotion Regulation Repertoirementioning
confidence: 99%
See 1 more Smart Citation
“…However, some researchers have argued that focusing on specific strategies may be problematic for understanding the everyday use of a broad range of explicit emotion regulation strategies (Aldao & Nolan-Hoeksema, 2013). One recent experience sampling study (Heiy & Cheavens, 2014) identified approximately 40 strategies that adult participants (aged 18-31) reported using over the course of the study for the regulation of both Page 24 of 49 A c c e p t e d M a n u s c r i p t 24 negative and positive states (summarised in Table 2). Indeed it is often necessary to regulate positive as well as negative states, e.g.…”
Section: Page 23 Of 49mentioning
confidence: 98%